ANALISIS HUKUM TENAGA KERJA ANAK DI SEKTOR KELAPA SAWIT DI INDONESIA - Widayanti Widayanti; Mig Irianto Legowo (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2022)
Child labor is a form of exploitation in employing minors for small wages. Child labor often occurs in the informal sector, such as the palm oil industry, due to the absence of formal recruitment and proper supervision of the company. Law Number 13 of 2003 concerning Manpower expressly prohibits the exploitation of children for economic motives. The purpose of this study: 1) to find out the condition of casual daily workers in the oil palm sector in Indonesia, 2) to find out the factors that influence the existence of child labor in the oil palm sector in Indonesia. 3) find out the legal efforts taken to tackle child labor in the oil palmsector in Indonesia. This study uses a normative juridical methodology by analyzing relevant studies and research on the research topic. The data obtained in this study are secondary data through journals, news, reports, and data officially published by the relevant agencies. The results showed that the underlying factors of child labor are economic, social, cultural, and educational. The efforts made in overcoming child exploitation are in the form of providing supervision and warning to companies.